Molecular and pathological identification of feline coronavirus type I - Amer, Alazawy; Arshad, Siti Suri; Bejo, Mohd Hair; Omar, Abdul Rahman; Tengku Ibrahim, Tengku Azmi; Bande, Faruku; Ajwad, Assumaidaee (Academic Journals, 2012)
The coronavirus in cats has been described as feline infectious peritonitis (FIPV) and feline enteric coronavirus (FECV). FIPV is highly fatal and caused immune-mediated pyogranulomatous disease, whereas FECV causes mild enteric infection. In this study, we described the isolation and molecular characterization of naturally occurring feline coronavirus from domestic cat in Malaysia. Additionally, the resultant pathological conditions observed in the infected cat were reported. Ascitic fluid sample was collected from 3-year-old domestic cat clinically suspected of effusive (wet form) FIP and subjected to virus isolation in Felis catus whole fetus cell cultures (Fcwf-4). The result of virus isolation was confirmed using one step reverse transcription polymerase chain reaction (RT-PCR). To gain insight on the genetic variant of FCoV, the S-gene sequence was amplified using type 1 specific primers.Virus isolation showed cytopathic effect (CPE) characterized by giant cells, ballooning and cells detachment. Ultrastructural findings showed virus particles attached to plasma membrane and later invaginated from the cell membrane. Virus-like particles were also observed in the vacuoles, likely as a result of spillage of mature virus-like particles into the cytoplasmic matrix. Histopathological examination of kidney, spleen and intestine organ samples revealed coagulative necrosis with infiltration of neutrophils and mononuclear cells. In conclusion, this study reports the first isolation of feline coronavirus in Malaysian cats and importantly the isolated virus was confirmed to be type I using S-gene amplification.